The Imaging Features and Diagnostic Value of Computerised Tomography in Seminal Duct Tuberculosis - Qi M; Zhang L; Gan W; Xu Y; Wei J; Fu X; Li X (Journal of Multidisciplinary Healthcare, 2023)
Min Qi,1,* Le Zhang,2,* Wei Gan,1 Yanling Xu,1 Jialu Wei,1 Xuwen Fu,1 Xiang Li1 1Department of Radiology, The Third People’s Hospital in Kunming/Yunnan Clinical Medical Center for Infectious Diseases, Kunming, 650041, People’s Republic of China; 2Department of ICU, The Third People’s Hospital in Kunming/Yunnan Clinical Medical Center for Infectious Diseases, Kunming, 650041, People’s Republic of China*These authors contributed equally to this workCorrespondence: Xiang Li, Department of Radiology, The Third People’s Hospital in Kunming/Yunnan Clinical Medical Center for Infectious Diseases, No. 319 of Wujing Street, Guandu District, Kunming, 650041, People’s Republic of China, Tel +86 871 6352 3507, Fax +86 871 6351 4717, Email lxiang12121@126.comObjective: To analyse the computerised tomography (CT) imaging features and diagnostic value of seminal duct tuberculosis (TB).Methods: The imaging data of male patients with ejaculatory duct TB who underwent surgical treatment in our hospital from 1 January 2019 to 31 December 2019 were retrospectively analysed. Through CT images, seminal duct TB was divided into different types, and the CT image features of different types of TB were analysed. The differences in diagnosis between CT and pathological results were compared.Results: According to the CT manifestations of TB of the intrapelvic segment of seminal duct TB, this disease could be divided into an intra-tubular calcification type, a lumen dilatation and effusion type and a wall thickening type, among which 6 cases (15.8%) were intra-tubular calcification types, 14 cases (36.8%) were lumen dilatation and effusion types and 18 cases (47.4%) were wall thickening types. The diagnostic efficacy of CT in the diagnosis of ejaculatory duct TB: sensitivity = 63.89% (23/36), specificity = 80.01% (44/53), accuracy = 75.28% (67/89), positive predictive value = 51.87% (43/109), negative predictive value = 77.19% (44/57) and kappa = 0.558.Conclusion: CT has high sensitivity and specificity in the diagnosis of seminal duct TB. The classification of seminal duct TB using CT images is of great significance for the diagnosis and treatment of the disease.Keywords: seminal duct, tuberculosis, computerised tomography